2013
DOI: 10.1302/0301-620x.95b7.30537
|View full text |Cite
|
Sign up to set email alerts
|

Changes in tibial bone density measured from standard radiographs in cemented and uncemented total knee replacements after ten years’ follow-up

Abstract: Stress shielding resulting in diminished bone density following total knee replacement (TKR) may increase the risk of migration and loosening of the prosthesis. This retrospective study was designed to quantify the effects of the method of fixation on peri-prosthetic tibial bone density beneath cemented and uncemented tibial components of similar design and with similar long-term survival rates. Standard radiographs taken between two months and 15 years post-operatively were digitised from a matched group of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 22 publications
2
37
0
1
Order By: Relevance
“…In our study, no signi cant bone reduction in the proximal medial tibia was observed at 24 months after surgery, suggesting that the BMD is stable in this area. However, decreases in BMD of the proximal tibia have been reported to persist even at 10 years following surgery 20 . Although correction of FTA changes the load-bearing axis of the leg and causes stress shielding, it is unclear when stress shielding ends.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, no signi cant bone reduction in the proximal medial tibia was observed at 24 months after surgery, suggesting that the BMD is stable in this area. However, decreases in BMD of the proximal tibia have been reported to persist even at 10 years following surgery 20 . Although correction of FTA changes the load-bearing axis of the leg and causes stress shielding, it is unclear when stress shielding ends.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of patients with end-stage osteoarthritis are receiving treatment with total knee arthroplasty (TKA), which is a successful procedure for alleviating pain, improving functional ability, and enhancing quality of life [1]. Bone mineral density (BMD) is an indicator of bone quality and re ects the material properties, bone metabolism and risk of fracture [2,3]. Postoperative changes in the periprosthetic bone density in the tibia are closely related to the outcomes of TKA.…”
Section: Introductionmentioning
confidence: 99%
“…Dual X-ray absorptiometry (DXA) is the gold standard clinical method used to evaluate BMD, but it is not used in routine examinations after TKA due to not only the absence of this technology in many hospitals with limited resources but also the high cost of the technology. Several studies have reported that the grayscale values measured on standard radiographs are closely related to BMD and can re ect changes in BMD [2,8]. Hernandez-Vaquero et al [8] revealed a method based on digital radiological densitometry to evaluate bone density using X-ray images.…”
Section: Introductionmentioning
confidence: 99%
“…Среди всех причин ревизионных опе-раций на долю асептического расшатывания имплан-тата приходится от 60 % до 73,8 % [2,10]. Развитие столь раннего остеолиза после замены сустава на ис-кусственный некоторые авторы связывают с наличием недостаточной физиологической нагрузки на поражен-ный коленный сустав вследствие имеющихся сгиба-тельных контрактур и приема нестероидных противо-воспалительных средств, оказывающих тормозящее влияние на функцию остеобластов [3,5,11].…”
unclassified